2021
DOI: 10.35741/issn.0258-2724.56.1.30
|View full text |Cite
|
Sign up to set email alerts
|

The Zero Fraud Implementation through the Innovation of Information Technology and Organizational Culture

Abstract: Indonesia has implemented the National Health Insurance (JKN) program since 2014. The Corruption Eradication Commission (KPK) detected fraud in the program, which causes state losses. Prevention by the Social Security Administering Bodies (BPJS), law enforcers, and health care facility providers (faskes) has proven not optimal yet. This study aims to determine the effect of Information Technology Innovation and Organizational Culture on fraud prevention in the Regional General Hospitals (RSUD) in Sumatra with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…IT can provide the facilities to improve decision making processes by enabling information collection, accounting, storage, and communication, thus empowering executives and stakeholders in making quality decisions. The current development of IT has resulted in every community having broad access to services and information to obtain services from a variety of organizations that are transparent, collaborative, accountable, and open (Ferina et al, 2021). E-government is an effective tool to reduce corruption by encouraging good governance and strengthening reform-oriented actors (Abraham, 2012).…”
Section: Hypothesis Development and Research Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…IT can provide the facilities to improve decision making processes by enabling information collection, accounting, storage, and communication, thus empowering executives and stakeholders in making quality decisions. The current development of IT has resulted in every community having broad access to services and information to obtain services from a variety of organizations that are transparent, collaborative, accountable, and open (Ferina et al, 2021). E-government is an effective tool to reduce corruption by encouraging good governance and strengthening reform-oriented actors (Abraham, 2012).…”
Section: Hypothesis Development and Research Frameworkmentioning
confidence: 99%
“…Corruption is a form of dishonesty or criminal offense undertaken by a person or organization entrusted with a position of authority, to acquire illicit benefit or abuse power for one's private gain. Corruption can be manifested at different levels which hinders good governance and administrative practices, and this can cause anger on the part of the victims of corruption and society (Graycar & Villa, 2011;Ferina et al, 2021). Lukito (2015) showed that the role of the private sector in the financial system can be seen as a non-criminal policy, which has a large impact as a method of prevention to fight economic crime, such as corruption, in promoting integrity and good corporate governance.…”
Section: The Effect Of Fraud Prevention On Good Public Governancementioning
confidence: 99%
See 2 more Smart Citations
“…Some subcultures are also present within an organization that are typically defined by the department designations and via geographical separations [24]. There are always some core values in an organization that are primary or dominant values accepted throughout an organization [25]. Culture is so essential for a technology organization as it defines the clear-cut boundaries present between one organization and others [26].…”
Section: Introductionmentioning
confidence: 99%